Long-term occupational trajectories and suicide: a 22-year follow-up of the GAZEL cohort study - Marine Azevedo Da Silva; Nadia Younès; Ariane Leroyer; Laurent Plancke; Cédric Lemogne; Marcel Goldberg; Mathieu Rivière; Maria Melchior (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVE: Most suicides occur among individuals of working age. Risk is elevated in some occupational groups, however relations between long-term occupational trajectories and suicide are not well known. We describe career-long occupational trajectories and examine their influence on suicide. METHODS: Data come from GAZEL, a French cohort study set among employees of a large national utilities company. Occupational grade was obtained from company records from the time of hiring (1953‒1988). Group-based trajectory models were used to define occupational trajectories over a mean time period of 25.0 (standard deviation 6.5) years. Causes of mortality, coded using the International Classification of Diseases, were recorded from 1993‒2014 and studied using Cox regression models. RESULTS: Of the 20 452 participants included in the study, 73 died by suicide between 1993‒2014. Results suggested an increased risk of suicide [hazard ratio (HR) 2.57, 95% confidence interval (CI) 1.08-6.15] among participants with persistently low occupational grade compared to those with higher occupational grade and career development. After adjustment for all covariates, especially psychological factors, this association was reduced and no longer statistically significant (HR 2.02, 95% CI 0.82-4.95). CONCLUSIONS: Persistently low occupational grade could be related to an elevated risk of suicide. This association partly reflects psychological and health characteristics, which can influence occupational trajectories and be reinforced by unfavorable work conditions.